DESIGN OF AN INTELLIGENT LINE-FOLLOWING AND MAZE-SOLVING ROBOT BASED ON FUZZY LOGIC AND ARDUINO - Pham, Truong-Phuong-Nam; Nguyen, Minh-Khoa; Lieu, Vinh-Hung; Nguyen, Thi-Ngoc-Thao; Nguyen, Thanh-Binh; Nguyen, Van-Hiep; Le, Thi-Hong-Lam; Tran, Trong-Bang; Do, Ngoc-Huy; Nguyen, Binh-Hau (Asosiasi Peneliti Sriwijaya, 2026)
This paper presents the design and implementation of an intelligent line-following and maze-solving robot based on fuzzy logic and an Arduino platform. The proposed system integrates infrared sensors for line detection, a fuzzy-PID control strategy for motion regulation, and a decision-making algorithm for maze navigation. The control approach was first validated through MATLAB/Simulink simulation and subsequently implemented on a physical robotic prototype. Experimental results conducted on a maze-structured track demonstrate stable line-tracking performance, smooth curve negotiation, accurate intersection handling, and precise stopping at the finish point. The results confirm that the proposed fuzzy-based control strategy enhances tracking accuracy, reduces oscillations, and improves overall robustness, proving its effectiveness and practicality for intelligent mobile robotic applications.